INNOVATION OF HIGHER EDUCATIONAL DEVELOPMENT IN UKRAINE AS THE BASIS OF FORMING THE PLANETARY THINKING OF THE FUTURE FACTOR - Лузік, Е. В.; Хоменко-Семенова, Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The research is devoted to the theoretical substantiation and practical implementation of the innovation chain "education - research - educational projects - innovation development" in the preparation of future researchers-specialists of the high technical school, able to navigate in vast amounts of information, critically evaluate them, possessing planetary thinking, make responsible decisions in modern globalized world. It is determined that understanding the present situation, prospects and vectors of the modern system of higher technical education requires a constructivist understanding of the entire educational process of higher education, which should focus not on the transfer of static knowledge, but to form innovative technology of work with information on which students can receive their own and adequate knowledge of today's pace of world development, to form integrated skills and intellectual skills. It is proved that the main changes in the construction of higher technical education should be based on principles similar to the principles of business building and knowledge orientation, which really bring success in modern society, and the basic conditions for the development of planetary thinking in the process of vocational training in VTZZ are: the formation of critical thinking and ability to solve problems, creativity and innovative skills, ability to cooperate, informational education, contextual learning skills.